우편업무조직에 있어 리더십과 조직몰입 및 직무만족과의 관계 - 남정우(Jung-Woo Nam); 최호택(Ho-Taek Choi); 류상일(Sang-Il Ryu) (한국콘텐츠학회 논문지, 9(5), 2009)
This study gropes for the way to seek a desirable leader increase the efficiency of the mail service in the post service administration. That is to say, this study presents an appropriate leadership for the enhancement of the post service administration by investigating the relationship of the leadership to the organizational commitment and job satisfaction in the post service organization. Consequently, for the mail business organization, the selling leadership and the participating leadership show strong positive (+) interrelationship with the organizational commitment, but weak positive (+) interrelationship with job satisfaction. On the other hand, the telling leadership and the delegating leadership show weak negative (-) interrelationship with the former. Here, we can learn that the selling leadership and participating leadership are more effective on the mail business organization. 본 연구는 우정사업 중 우편업무의 효과성을 높이기 위해서는 어떠한 리더가 필요한가를 모색해보고자 하였다. 즉, 우편업무조직을 중심으로 하여 리더십과 우편조직에 있어 조직몰입 및 직무만족과의 관계를 살펴서, 향후 우정사업 서비스의 향상을 위한 리더(지도자)를 제시해 보고자 하였다. 이러한 연구목적을 달성하기 위하여 허시와 블랜차드(Horsey & Blanchard)의 '상황적 리더십 이론'을 중심으로 하여, '지시적 리더(telling)', '설득적 리더 (selling)', '참여적 리더(participating)', 그리고 '위임적 리너 (delegating)'로 구분을 통하여 리더십유형에 따라 우편업무조직의 조직몰입과 직무만족에 어떠한 영향을 주는지를 도찰하였다. 결론적으로 우편업무조직에 있어서는 설득형 리더십과 참가형 리더십이 조직몰입에 강항 정(+)의 상관 관계를 보였고, 직무만족에는 약한 정(+)의 상관성을 보였다. 반면 지시형 리더십과 위양형 리더십은 약한 부(-)의 상관성을 보였다. 여기서 알 수 있듯이 우편업무조직에서는 설득형과 참가형 리더십이 보다 효과 적이라는 것을 알 수 있었다.